Anti-inflammatory activity of argan oil and its minor components. (2nd April 2020) - Menni, Hanane Ben; Belarbi, Meriem; Menni, Dounia Ben; Bendiab, Hadjer; Kherraf, Yamina; Ksouri, Riadh; Djebli, Noureddine; Visioli, Francesco
Abstract: Argan oil is thought to be the most expensive edible oil worldwide. It is difficult to produce and the argan tree only grows in a limited geographical area, notably Morocco and Algeria. Because it is produced by mechanical means, argan oil contains "minor" components that might be endowed with healthful effects. We investigated in vivo the anti-inflammatory activities of argan oil and its unsaponifiable fraction, using diclofenac as the control, in a carrageenan-induced rat model of inflammation. Rats were given different amounts of argan oil or its unsaponifiable fraction, by gavage. We report that argan oil and its "minor" components effectively lessen the inflammatory actions of carrageenan. Far from being "pharmacological" the actions of argan oil are comparable with those of diclofenac in the short, i.e. 4 h term. Sustained consumption of argan oil might, therefore, contribute to lessen the burden of degenerative diseases associated with higher inflammatory status.